Contexts of midwifery practice - Muscat, Helen; Passmore, Heather; Chenery-Morris, Sam (Los Angeles : SAGE Publications ; London : Learning Matters, 2015)
In order to become skilled and competent practitioners, student midwives need to understand the complex individual, family and societal issues they will encounter. By introducing the contemporary context of midwifery practice, this book helps students to understand the problems many women face in society.--
The principles of health promotion and salutogenesis -- Weight management in pregnancy -- Age and childbearing -- Women who have communication challenges -- Sexual and reproductive health in childbearing -- Perinatal mental health -- Domestic abuse -- Substance misuse and pregnancy -- Promoting parenting in midwifery.
Keywords: Obstetrics; Midwives; Midwifery; Childbirth; Maternal health services; Midwifery; Home Childbirth; Maternal Health Services; Midwifery; Childbirth; Maternal health services; Midwifery; Midwives; Obstetrics